Evaluation of sintered hydroxyapatite (HA) via powder injection molding - Nashrah Hani Jamadon,; Nurul Izaan Abdullah Halid,; Abu Bakar Sulong,; Mohd Hamdi Abd Shukor,; Miyashita, Yukio (Penerbit Universiti Kebangsaan Malaysia, 2020)
Hydroxyapatite (HA), a ceramic phosphate with good biocompatibility, has been extensively used in the field of bone replacement, both in orthopedics and in dentistry. Desired molded part of HA is fabricated by using powder injection molding (PIM) method. Powder loading, rheological properties and sintering atmosphere can significantly affect the quality of molded HA. The effect of these factors on the microstructure and mechanical properties of powder injection molded HA were investigated. Different powder loading of HA (54, 55 and 56 vol%), were mixed with binder 40 wt.% of palm stearin and 60 wt.% polyethylene. The temperature injection were set at 150°C, 160°C and 170°C with the pressure injection of 12 bar. The green body were then sintered in the furnace at temperature of 1100°C, 1200°C and 1300°C for 4 hours. Analysis of variance (ANOVA) is used to determine the optimization of injection molding. Based on the analysis, it was found that 56 vol% powder loading, temperature injection at 150°C up to 170°C and 12 bar pressure injection are the optimum parameters for the process of injection molding. Results further demonstrate that the optimum condition involves the specified HA with temperature injection at 170°C and sintered at 1300°C provides the highest hardness value and flexural strength of 690 Hv and 17.75 MPa respectively.